EVA (Ethylene Vinyl Acetate) foam reclaimed material-alpha-methacrylic acid copolymer as well as preparation method and application thereof
By grafting α-methacrylic acid on the surface of the EVA foam recovery material, the problems of high energy consumption and unstable effect during the treatment of EVA foam recovery material in the prior art are solved, and higher compatibility and functionality are achieved, which is suitable for industrial production.
Patent Information
- Application Number
- CN202510120104.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-25
- Publication Date
- 2025-04-22
AI Technical Summary
The prior art has problems of high energy consumption and unstable effect when dealing with EVA foam recycling materials, and it is difficult to effectively improve the compatibility of the recycling materials with the new polymer matrix.
By grafting α-methacrylic acid on the surface of the EVA foam recovery material, a stronger interaction is formed, thereby enhancing its compatibility and functionality in the composite material. This method uses water as the reaction medium, simplifying the process and reducing the use of organic solvents.
It significantly improves the compatibility and functionality of EVA foam recycling materials, improves its mechanical properties, thermal stability and weather resistance, is suitable for large-scale industrial production, and reduces production costs and environmental burdens.
Smart Images

Figure CN119859221A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of modified EVA, and in particular relates to an EVA foam recycled material-alpha-methacrylic acid copolymer and a preparation method and application thereof. Background Art
[0002] With the rapid development of industry and social economy, EVA (ethylene-vinyl acetate copolymer) is widely used as a polymer material due to its good plasticity, elasticity and processability. In particular, EVA materials after foaming have the advantages of low density, excellent mechanical properties, easy coloring, etc., and are therefore often used to manufacture various foamed sole materials. However, in the production process of EVA foam materials and their products, due to the requirements of size and shape, a large amount of scraps and defective products will inevitably be produced. These waste materials already contain a variety of auxiliary materials such as fillers, colorants, rubber and plastic additives. Due to the complex composition of EVA foam materials, it is difficult to achieve efficient recycling and reuse. Therefore, it is of great practical significance to develop efficient EVA foam recycled material processing and reuse technology.
[0003] The molecular chains of EVA foam materials form a highly cross-linked three-dimensional network structure during the foaming process. This structure gives the foam material the characteristics of heat resistance, corrosion resistance, and infusibility, but it also makes the recycling and reuse of EVA foam recycled materials face huge challenges. In general recycling and reuse technology, EVA foam recycled materials are usually compounded with new polymers to form composite materials. In this technology, the interaction strength between the recycled EVA and the matrix directly determines the performance of the composite material. Ideally, it is hoped that the recycled EVA can form a strong interaction with the matrix. However, EVA foam recycled materials are usually cross-linked, structurally stable and inert, resulting in poor compatibility with the matrix. When the amount of recycled EVA added increases, the mechanical properties of the composite material tend to decrease.
[0004] In order to solve this problem, some researchers have tried to process EVA foam recycling materials by high-temperature shearing or melt extrusion. For example, CN118085437A discloses a recycling method based on the de-crosslinking of EVA foam recycling materials and its application. The method expands the three-dimensional cross-linked network of EVA foam recycling materials by a solvent expansion method, and then uses 2,2'-dithiodibenzoic acid as a de-crosslinking agent to make it evenly penetrate into the cross-linked network in the solvent. Through the high-temperature shearing action of equipment such as a twin-screw extruder, the sulfur free radicals generated by the de-crosslinking agent combine with the active free radicals generated when the cross-linked network is destroyed, thereby obtaining de-crosslinked EVA foam recycling materials. This process can improve the compatibility of recycled EVA with the new polymer matrix to a certain extent, and achieve a better recycling and reuse effect, but its energy consumption is high.
[0005] In addition, CN114835973A proposes a kind of EVA composite foam material prepared based on EVA foam recycled material and its preparation process. The method modifies the EVA foam recycled material by thermoplastic starch and maleic anhydride grafted high-density polyethylene (HDPE), and utilizes extrusion granulation technology to blend and melt EVA resin, styrene-ethylene-butylene-styrene block copolymer (SEBS) and modified EVA foam recycled material, and finally obtains EVA composite foam material. The essence of this method is to improve the compatibility of recycled EVA with other polymer components by maleic anhydride grafting modification. However, this process is also relatively energy-consuming, and the improvement effect is not stable enough.
[0006] In summary, although there are currently many methods trying to solve the problem of recycling EVA foam recycled materials, the existing technology still has shortcomings such as high energy consumption and unstable effect. Summary of the invention
[0007] The present invention aims to overcome the defects of the prior art and provide an EVA foam recycled material-alpha-methacrylic acid copolymer.
[0008] Another object of the present invention is to provide a method for preparing the above-mentioned EVA foam recycled material-α-methacrylic acid copolymer.
[0009] Another object of the present invention is to provide an application of the above-mentioned EVA foam recycled material-α-methacrylic acid copolymer.
[0010] The technical solution of the present invention is as follows:
[0011] An EVA foam recycled material-α-methacrylic acid copolymer, with a grafting degree of 0.6-7.3%, is prepared by mixing and drying the following raw material components in parts by weight:
[0012] 2 parts by weight of powdered EVA foam recycled material
[0013] Initiator 0.03-0.1 parts by weight
[0014] Methacrylic acid monomer 0.8-1.6 parts by weight
[0015] 20 parts by weight of deionized water.
[0016] In a preferred embodiment of the present invention, the initiator is selected from benzoyl peroxide (BPO), dicumyl peroxide (DCP) and tert-butyl peroxy-2-ethylhexyl carbonate.
[0017] More preferably, the initiator is benzoyl peroxide.
[0018] The preparation method of the above-mentioned EVA foam recycled material-α-methacrylic acid copolymer comprises the following steps:
[0019] (1) preparing a pre-reaction mixed solution by mixing powdered EVA foam recycled material, deionized water, an initiator and methacrylic acid monomer;
[0020] (2) placing the pre-reaction mixed solution obtained in step (1) under nitrogen protection and heating to react;
[0021] (3) The reaction product obtained in step (2) is washed and filtered for multiple times, and then dried to obtain the EVA foam recycled material-α-methacrylic acid copolymer.
[0022] In a preferred embodiment of the present invention, in step (2), the temperature is heated to 70-95° C. and the reaction is carried out for 1-6 hours.
[0023] More preferably, in step (2), the temperature is heated to 75-95° C. and the reaction is carried out for 1-2 hours.
[0024] The above EVA foam recycled material-α-methacrylic acid copolymer is used as a shoe material.
[0025] In a preferred embodiment of the present invention, the shoe material comprises a shoe base material and a shoe fabric.
[0026] A pair of shoes comprises the EVA foam recycled material-alpha-methacrylic acid copolymer.
[0027] The beneficial effects of the present invention are:
[0028] 1. The surface of the EVA foam recycled material of the present invention is grafted with α-methacrylic acid, and this chemical structure gives the material extremely high activity and polarity; due to the introduction of α-methacrylic acid, the EVA foam recycled material can form a stronger interaction with other components, thereby significantly improving its compatibility and functionality in the composite material. In addition, the grafting method is simple and green and environmentally friendly, which has extremely important application significance for the reuse of EVA foam recycled materials.
[0029] 2. The present invention uses water as the reaction medium, completely abandoning the organic solvents used in large quantities in the traditional process. This improvement not only reduces the environmental pollution caused by the volatilization of organic solvents, but also reduces the safety risks in the production process.
[0030] 3. Through the grafting reaction, the present invention can effectively improve the mechanical properties, thermal stability and weather resistance of EVA foam recycling materials. The grafted EVA foam recycling materials show more excellent comprehensive performance in subsequent applications, can meet higher standard industrial needs, and thus broaden its application scope.
[0031] 4. The grafting reaction of the present invention is carried out under aqueous conditions, the reaction conditions are mild, and no high temperature, high pressure or complex equipment support is required. This reaction method can easily graft methacrylic acid onto EVA foam recycled materials, the reaction process is simple and feasible, easy to operate and control, energy-saving and environmentally friendly, and low-cost, and suitable for large-scale industrial production.
[0032] 5. In the grafting process, the present invention generates relatively few by-products. This feature not only simplifies the complexity of waste treatment, but also reduces the generation of waste, further reducing production costs and environmental burdens. BRIEF DESCRIPTION OF THE DRAWINGS
[0033] Figure 1 The present invention is a flow chart of the preparation process of an embodiment of the present invention.
[0034] Figure 2 This is a graph showing infrared test results of the methacrylic acid modified EVA foam recycled material prepared in Example 1 of the present invention, the EVA foam recycled material not modified with methacrylic acid in Comparative Example 1, and polymethacrylic acid.
[0035] Figure 3 The thermogravimetric test results of the methacrylic acid modified EVA foam recycled material prepared in Examples 1 and 6 of the present invention, the EVA foam recycled material not modified with methacrylic acid in Comparative Example 1, and polymethacrylic acid are shown.
[0036] Figure 4 The water contact angle test results of the methacrylic acid modified EVA foam recycled material prepared in Example 1 of the present invention and the EVA foam recycled material not modified with methacrylic acid in Comparative Example 1 are shown in the figure on the left. DETAILED DESCRIPTION
[0037] The technical solution of the present invention is further illustrated and described below through specific implementation modes in combination with the accompanying drawings.
[0038] The preparation process of the following examples is as follows Figure 1 As shown, the grafting degree = (weight gain of EVA foam recycled material / original weight of EVA foam recycled material) × 100%.
[0039] Example 1
[0040] (1) Weigh 2 g of powdered EVA foam recycled material (300 mesh) and prepare a pre-reaction mixed solution with 20 g of deionized water, 0.1 g of benzoyl peroxide and 1.6 g of methacrylic acid monomer;
[0041] (2) placing the pre-reaction mixed solution obtained in step (1) under nitrogen protection, heating to 75° C., and reacting at 75° C. for 1.5 h;
[0042] (3) washing and filtering the reaction product obtained in step (2) for multiple times, and then drying it in a constant temperature drying oven to obtain EVA foam recycled material-α-methacrylic acid copolymer.
[0043] The grafting degree of the EVA foam recycled material-α-methacrylic acid copolymer prepared in this example was measured by weight gain method, and the grafting degree was measured to be 4.85%.
[0044] Example 2
[0045] (1) Weigh 2 g of powdered EVA foam recycled material (200 mesh) and prepare a pre-reaction mixed solution with 20 g of deionized water, 0.1 g of benzoyl peroxide and 1.6 g of methacrylic acid monomer;
[0046] (2) placing the pre-reaction mixed solution obtained in step (1) under nitrogen protection, heating to 85° C., and reacting at 85° C. for 1.5 h;
[0047] (3) washing and filtering the reaction product obtained in step (2) for multiple times, and then drying it in a constant temperature drying oven to obtain EVA foam recycled material-α-methacrylic acid copolymer.
[0048] The grafting degree of the EVA foam recycled material-α-methacrylic acid copolymer prepared in this example was measured by weight gain method, and the grafting degree was measured to be 6.35%.
[0049] Example 3
[0050] (1) Weigh 2 g of powdered EVA foam recycled material (400 mesh) and prepare a pre-reaction mixed solution with 20 g of deionized water, 0.1 g of benzoyl peroxide and 1.6 g of methacrylic acid monomer;
[0051] (2) placing the pre-reaction mixed solution obtained in step (1) under nitrogen protection, heating to 95° C., and reacting at 95° C. for 1.5 h;
[0052] (3) washing and filtering the reaction product obtained in step (2) for multiple times, and then drying it in a constant temperature drying oven to obtain EVA foam recycled material-α-methacrylic acid copolymer.
[0053] The grafting degree of the EVA foam recycled material-α-methacrylic acid copolymer prepared in this example was measured by weight gain method, and the grafting degree was measured to be 7.25%.
[0054] get
[0055] Example 4
[0056] (1) Weigh 2 g of powdered EVA foam recycled material (20 mesh), and prepare a pre-reaction mixed solution with 20 g of deionized water, 0.1 g of benzoyl peroxide and 1 g of methacrylic acid monomer;
[0057] (2) placing the pre-reaction mixed solution obtained in step (1) under nitrogen protection, heating to 75° C., and reacting at 75° C. for 1.5 h;
[0058] (3) washing and filtering the reaction product obtained in step (2) for multiple times, and then drying it in a constant temperature drying oven to obtain EVA foam recycled material-α-methacrylic acid copolymer.
[0059] The grafting degree of the EVA foam recycled material-α-methacrylic acid copolymer prepared in this example was measured by weight gain method, and the grafting degree was 3.76%.
[0060] Example 5
[0061] (1) Weigh 2 g of powdered EVA foam recycled material (100 mesh) and prepare a pre-reaction mixed solution with 20 g of deionized water, 0.1 g of benzoyl peroxide and 0.8 g of methacrylic acid monomer;
[0062] (2) placing the pre-reaction mixed solution obtained in step (1) under nitrogen protection, heating to 75° C., and reacting at 75° C. for 1.5 h;
[0063] (3) washing and filtering the reaction product obtained in step (2) for multiple times, and then drying it in a constant temperature drying oven to obtain EVA foam recycled material-α-methacrylic acid copolymer.
[0064] The grafting degree of the EVA foam recycled material-α-methacrylic acid copolymer prepared in this example was measured by weight gain method, and the grafting degree was measured to be 3.1%.
[0065] get
[0066] Example 6
[0067] (1) Weigh 2 g of powdered EVA foam recycled material (400 mesh) and prepare a pre-reaction mixed solution with 20 g of deionized water, 0.06 g of benzoyl peroxide and 1.6 g of methacrylic acid monomer;
[0068] (2) placing the pre-reaction mixed solution obtained in step (1) under nitrogen protection, heating to 75° C., and reacting at 75° C. for 1.5 h;
[0069] (3) washing and filtering the reaction product obtained in step (2) for multiple times, and then drying it in a constant temperature drying oven to obtain EVA foam recycled material-α-methacrylic acid copolymer.
[0070] The grafting degree of the EVA foam recycled material-α-methacrylic acid copolymer prepared in this example was measured by weight gain method, and the grafting degree was measured to be 2.37%.
[0071] Example 7
[0072] (1) Weigh 2 g of powdered EVA foam recycled material (250 mesh), and prepare a pre-reaction mixed solution with 20 g of deionized water, 0.03 g of benzoyl peroxide and 1.6 g of methacrylic acid monomer;
[0073] (2) placing the pre-reaction mixed solution obtained in step (1) under nitrogen protection, heating to 75° C., and reacting at 75° C. for 1.5 h;
[0074] (3) washing and filtering the reaction product obtained in step (2) for multiple times, and then drying it in a constant temperature drying oven to obtain EVA foam recycled material-α-methacrylic acid copolymer.
[0075] The grafting degree of the EVA foam recycled material-α-methacrylic acid copolymer prepared in this example was measured by weight gain method, and the grafting degree was measured to be 0.6%.
[0076] Comparative Example 1
[0077] EVA foam recycled material without methacrylic acid modification
[0078] A. Infrared testing was performed on the methacrylic acid modified EVA foam recycled material obtained in Example 1 and the EVA foam recycled material and polymethacrylic acid not modified with methacrylic acid in the comparative example. The results are as follows: Figure 2 As shown, the main absorption bands of EVA recycled materials can be observed, namely those related to acetate groups and vinyl groups. Figure 2 In the absorption band of PMAA, it can be observed at 1695cm -1 There is an absorption peak at 966cm, which represents the characteristic absorption band of the carbonyl (C=O) double bond on methacrylic acid. After the grafting reaction, compared with the original EVA recycled material, it can be clearly seen that the grafted sample has a peak at 966cm -1 A new peak appeared at 1695cm -1 New peaks appeared on the left and right EVA recycled materials, which are also the characteristic absorption peaks of C=O existing on methacrylic acid, indicating that methacrylic acid was successfully connected to the EVA recycled material.
[0079] B. The methacrylic acid modified EVA foam recycled materials obtained in Examples 1 and 6 and the EVA foam recycled materials and polymethacrylic acid not modified with methacrylic acid in Comparative Example 1 were subjected to thermogravimetric testing. The results are shown in FIG. Figure 3As shown in the figure, the first weight loss of EVA recycled material between 300 and 360°C is related to the decomposition of vinyl acetate. At temperatures above 420°C, a second weight loss occurs, which is related to the decomposition of the ethylene part in the EVA copolymer. PMAA has a 20% mass loss at 200-250°C, indicating the degradation of the carboxyl group of PMAA, while the remaining mass loss at 400°C is related to the thermal decomposition of the PMAA main chain. The MAA-grafted EVA recycled material sample began to lose mass at 200°C, and a second mass loss occurred at 400°C, with the same mass loss platform, indicating that MAA was successfully grafted to the EVA foam. And with the increase of the grafting amount, the thermal stability of EVA recycled material decreases accordingly.
[0080] C. The water contact angle test was performed on the methacrylic acid modified EVA foam recycled material obtained in Example 1 and the EVA foam recycled material not modified with methacrylic acid in the comparative example. The results are as follows: Figure 4 As shown in the figure, by testing the water contact angle of EVA recycled material and grafted EVA recycled material, it can be found that the water contact angle of EVA recycled material after grafting methacrylic acid is reduced, because the added methacrylic acid surface contains oxygen-containing functional groups such as hydroxyl and carboxyl, and the presence of these hydrophilic groups improves the hydrophilicity of the EVA recycled material itself.
[0081] The above description is only a preferred embodiment of the present invention, and therefore cannot be used to limit the scope of the present invention. That is, equivalent changes and modifications made according to the patent scope of the present invention and the contents of the specification should still fall within the scope of the present invention.
Claims
1. An EVA foam recycled material-α-methacrylic acid copolymer, characterized in that: The grafting degree is 0.6-7.3%, and the raw material components including the following parts by weight are mixed and dried: 2 parts by weight of powdered EVA foam recycled material Initiator 0.03-0.1 parts by weight Methacrylic acid monomer 0.8-1.6 parts by weight 20 parts by weight of deionized water.
2. The EVA foam recycled material-α-methacrylic acid copolymer according to claim 1, characterized in that: The initiator is selected from benzoyl peroxide (BPO), dicumyl peroxide (DCP) and tert-butyl peroxy-2-ethylhexyl carbonate.
3. The EVA foam recycled material-α-methacrylic acid copolymer according to claim 2, characterized in that: The initiator is benzoyl peroxide.
4. The method for preparing the EVA foam recycled material-α-methacrylic acid copolymer according to any one of claims 1 to 3, characterized in that: The steps include: (1) preparing a pre-reaction mixed solution by mixing powdered EVA foam recycled material, deionized water, an initiator and methacrylic acid monomer; (2) placing the pre-reaction mixed solution obtained in step (1) under nitrogen protection and heating to react; (3) The reaction product obtained in step (2) is washed and filtered for multiple times, and then dried to obtain the EVA foam recycled material-α-methacrylic acid copolymer.
5. The preparation method according to claim 4, characterized in that: In the step (2), the temperature is heated to 70-95° C. and the reaction is carried out for 1-6 hours.
6. The preparation method according to claim 5, characterized in that: In the step (2), the temperature is heated to 75-95° C. and the reaction is carried out for 1-2 hours.
7. Use of the EVA foam recycled material-α-methacrylic acid copolymer described in any one of claims 1 to 3 as a shoe material.
8. The use according to claim 7, characterized in that: The shoe material comprises a shoe base material and a shoe fabric.
9. A shoe, characterized in that: The EVA foam recycled material-α-methacrylic acid copolymer according to any one of claims 1 to 3.
Citation Information
Patent Citations
EVA-methacrylic acid copolymer and grafting reaction extruding production method
CN104341557A
Toughened and enhanced polyethylene / polypropylene recycling composite material and preparation method thereof
CN108285512A
EVA / AA / MA grafted copolymer and preparation method thereof
CN109280131A
Foaming material prepared based on soybean oil thermal oxidation induction of waste EVA (Ethylene Vinyl Acetate) and preparation method thereof
CN117209882A
Decrosslinking modified elastomer regenerated material as well as regeneration method and application thereof
CN118420837A